A Transcategorial Conception of Dynamis and Energeia - Unlu, Hikmet (American catholic philosophical quarterly, 2023)
On the standard interpretation of Metaphysics IX, Aristotle proceeds from the original sense of δύναμις and ἐνέργεια to an ontological conception of these terms. This should raise the question of what is not ontological about the former and what is ontological about the latter. To address these questions I discuss the commentaries by Heidegger and Menn, which alone come close to addressing these issues. But their readings cannot neatly distinguish between the two senses of δύναμις and ἐνέργεια that we find in the Aristotelian text, thus compelling us to seek a better way of clarifying the standard interpretation, which I argue can be more precisely understood in the following way: δύναμις and ἐνέργεια in their customary meaning cannot be considered ontological in the sense that they have a particular locus among the categories, which is what sets them apart from their newer, ontological meaning. I conclude therefore that the text of Metaphysics IX can be understood as proceeding from an intracategorial conception of δύναμις and ἐνέργεια toward a transcategorial conception of these terms.